Validation of a Single-Platform, Volumetric, CD45-Assisted PanLeucogating Auto40 Flow Cytometer To Determine the Absolute Number and Percentages of CD4 T Cells in Resource-Constrained Settings Using Cameroonian Patients' Samples - Mbopi-Kéou, François-Xavier (American Society for Microbiology, 2012)
The study evaluated the single-platform, volumetric, CD45-assisted PanLeucogating Auto40 flow cytometer (Apogee Flow Systems Ltd., Hemel Hempstead, United Kingdom) for CD4 T cell numeration, compared to the reference FACSCalibur flow cytometer. Results of absolute counts and percentages of CD4 T cells by Auto40 and FACSCalibur of 234 tripotassium EDTA (K3-EDTA)-blood samples from 146 adults and 88 children (aged from 18 months to 5 years), living in Yaoundé, Cameroon, were highly correlated (r(2) = 0.97 and r(2) = 0.98, respectively). The mean absolute bias and relative bias between Apogee Auto40 and FACSCalibur absolute CD4 T cell counts were +9.6 cells/μl, with limits of agreement from −251 to 270 cells/μl, and +4.1%, with limits of agreement from −16.1 to 24.4%, respectively. The mean absolute bias and relative bias between Apogee Auto40 and FACSCalibur CD4 T cell results expressed as percentages were +0.05% CD4 (95% confidence interval [CI], −0.03 to 0.41), with limits of agreement from −6.0 to 5.9% CD4, and +1.0%, with limits of agreement from −32.3 to 34.4%, respectively. The Auto40 counting allowed identification of the majority of adults with CD4 T cell counts below 200 cells/μl (sensitivity, 87%; specificity, 98%) or below 350 cells/μl (sensitivity, 92%; specificity, 98%) and of children with CD4 T cell counts below 750 cells/μl (sensitivity, 82%; specificity, 98%) or below 25% CD4(+) (sensitivity, 96%; specificity, 99%). The Auto40 analyzer is a reliable alternative flow cytometer for CD4 T lymphocyte enumeration to be used in routine immunological monitoring according to the WHO recommendations for HIV-infected adults as well as children living in resource-constrained settings.